Pelatihan Pencegahan dan Penanganan Perundungan Siswa Bagi Guru BK di Kabupaten Gresik - Purwoko, Budi; Winingsih, Evi; Ghozali, Muhamad Afifuddin; Nurismawan, Ach. Sudrajad (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The rise of bullying cases in the Gresik Regency school environment is a basic problem that can interfere with student learning comfort. This phenomenon encourages BK teachers to have innovative prevention strategies and appropriate intervention methods to eradicate bullying. Training for Guidance and Counseling (BK) teachers in Gresik district emphasized the importance of special education and training to prevent and overcome student bullying in schools. This activity aims to improve counseling teachers' skills in identifying, managing and addressing bullying of various types, including verbal, physical and cyberbullying. By understanding effective strategies, counseling teachers can be more a,ctive in maintaining students' emotional health and well-being, and supporting a safe and harmonious school environment. This training activity also includes training on mediation skills and emotion regulation in the counseling process as an effort to provide appropriate interventions, not only for victims, but also for perpetrators. This community service activity has been successfully implemented through direct delivery of materials for 1 day at the RKB MTsN Gresik, and has met the target of increasing the understanding and identification ability of BK teachers in handling student bullying in Gresik Regency by 15% based on the analysis of Google forms distributed before and after the training.